Correlation in Energy Markets - Nina Lange (Copenhagen Business School (CBS), 2017)
In this paper, I study the relationship between volatility of crude oil prices and volatility of the EURUSD rate. If there is a common factor in the volatility of crude oil and the volatility of exchange rates, possible explanations could be that the financial crisis caused a volatility spillover between the two markets or that commodity markets, one of the most important being the crude oil market, are strengthening their connection with classic financial markets including exchange rate markets. I use an extensive data set of crude oil futures and options and EURUSD futures and options spanning a period from 2000 to 2012. This data allows me to analyse the marketperceived volatility rather than investigating volatilities in the form of realised returns. A model-free analysis supports the presence of a joint factor in the volatilities since mid-2007. As the two markets are asynchronous in futures and options maturity date, a term structure models allow for a description of the observed volatility surfaces by one or more stochastic volatility processes. A term structure model including one joint volatility factor and two market-specific volatility factors is proposed to capture the joint factor in the volatilities from 2007 onwards. The paper focuses on confirming the existence of a joint factor, but leaves out the explanation of where it comes from. As data only covers until 2012, there is not enough information post-crisis to distinguish whether the joint volatility is a financialization or a crisis effect – or a combination.
hdl:10398/9461
Keywords: 650